ONTOLOGICAL BASIS OF SCIENCE CLASSIFICATION (Study on the Philosophy of Islamic Education) - Salminawati Salminawati (Edukasi Islami: Jurnal Pendidikan Islam, 2020)
This paper aims to analyze the nature of science through scientific specifications. The focus of the discussion is the ontological basis of the classification of science in terms of studies in Islamic education philosophy. This research uses a qualitative approach with a literature study method. Scientific reference materials become the primary source in analyzing and testing the validity of research data. The results of this study indicate that the belief in the existence of an ontological status or the existence of objects of knowledge is what will become the ontological basis of the epistemology to be built. Which ontological basis is chosen will greatly influence and even determine the epistemological pattern it builds. For example, the distrust of some great Western scientists to the existence or ontological status of metaphysical entities, causing them to limit the subject matter of science (science) only to the empirical physical field which they call the positive world. Thus they also create a classification of science and scientific methods that match their ontological views. On the other hand, many Muslim scientists and philosophers (Al-Farabi, Al-Ghazali, and Ibn Khaldun) believe that what is real, is not only physical objects, but also non-physical entities (meta physical). In their view, metaphysical (immaterial) entities have an ontological status that is as strong or stronger as physical entities.